Reconstructing Rawls: the Kantian foundations of justice as fairness - Taylor, Robert S. (Pennsylvania State University Press, 2011)
"Compares the theories of John Rawls and Emmanuel Kant, and offers an internal critique and reconstruction of justice as fairness, reconceiving it as a comprehensive, universalistic Kantian liberalism"--Provided by publisher